Evaluation of impact of COVID-19 pandemic on the burden and pattern of severe malaria in Nigerian children - Bamidele, Olumuyiwa C.; Ezeonwu, Bertilla U.; Ajaegbu, Obinna C.; Joseph, Uzoma C. Ajanwenyi; Adaramola, Tosin S.; Anazor, Chioma V.; Abonyi, Leonard E.; Nwafor, Ifeoma O.; Okolo , Angela A. (International Journal Of Community Medicine And Public Health, 2023)
Background: Malaria is an infectious disease caused by the protozoan Plasmodium, accounting for 36% of under-five mortality. About 4.5% of all malaria-infected children reported at least one symptom of severe malaria, with worsening outcome. COVID-19 and malaria shared similar clinical presentation in children this similarity may lead to delay in initiation of treatment for malaria, with progression from uncomplicated to severe forms and consequently high mortality. Thus, we set out to study the extent COVID-19 impacted on the burden and pattern of severe malaria. Methods: It was a retrospective study of all the children admitted into the children’s emergency room severe malaria, from March 2018 to February 2022. The data collected included the total number of admissions within the period, the month and year of admission, age, gender, the component of severe malaria that was the final diagnosis and outcome of management. Data were analysed using NCSS 9 statistical software. Results: There were 4761 admissions within the study period: males were 54.7%, subjects 1-<60 months were 60.5% and pre COVID-19 period were 63.7%. The prevalence rates of severe malaria in CHER were 2.6%. Among those with severe malaria, the case fatality rate was 10.7%. Severe malarial anemia was the most common accounting for 49.2% and has predilection for the younger age. Cerebral malaria was predominantly diagnosed during the COVID-19 period. Conclusions: The prevalence of severe malaria was 2.6% and severe malaria anaemia was the most common mode of presentation while cerebral malaria was diagnosed more during the COVID-19 period.